Parents' perspectives on care of children with autistic spectrum disorder in South Asia – Views from Pakistan and India. (June 2015) - Minhas, Ayesha; Vajaratkar, Vivek; Divan, Gauri; Hamdani, Syed Usman; Leadbitter, Kathy; Taylor, Carol; Aldred, Catherine; Tariq, Ahmareen; Tariq, Mahjabeen; Cardoza, Percy; Green, Jonathan; Patel, Vikram; et al.
Abstract Autism spectrum disorder (ASD) affects about 1.4% of the population in South Asia but very few have access to any form of health care service. The objective of this study was to explore the beliefs and practices related to the care of children with ASD to inform strategies for intervention. In Pakistan, primary data were collected through in-depth interviews of parents (N = 15), while in India a narrative review of existing studies was conducted. The results show that the burden of care is almost entirely on the mother, leading to high levels of stress. Poor awareness of the condition in both family members and front-line health-providers leads to delay in recognition and appropriate management. There is considerable stigma and discrimination affecting children with autism and their families. Specialist services are rare, concentrated in urban areas, and inaccessible to the majority. Strategies for intervention should include building community and family support networks to provide respite to the main carer. In the absence of specialists, community members such as community health workers, traditional practitioners and even motivated family members could be trained in recognizing and providing evidence-based interventions. Such task-shifting strategies should be accompanied by campaigns to raise awareness so greater inclusivity can be achieved.